Language Barriers in Studying Medicine in English: Concerns and Attitudes of Clinical Phase Medical Students at the University of Tripoli - Ruya Almushwat,; Hajer Elkout, (AlQalam Journal of Medical and Applied Sciences, 2024)
Despite being a foreign language, English is the medium of instruction in many Arab medical schools, creating language barriers and difficulties for students. The aim of this study was to assess the concerns and attitudes of students towards English as a medium of instruction (EMI) and to explore the barriers as well as opinions of students. This was a cross-sectional descriptive study that targeted students enrolled at the clinical phase at the faculty of medicine in the University of Tripoli using a self-administered questionnaire during the period from the 10th of March 2024 to the 24th of March, 2024. About 61 (36.1%) medical students were moderately comfortable with the English language, followed by 45 (26.6%) who were comfortable as opposed to 10 (5.9%) who were very uncomfortable. The majority 102 (60.4%) recommended changes to address the language concerns in the curriculum. Among the 66 participants who responded to this section, 33.3% recommended that the university should provide free English language courses and 161 (95.3%) stated they would choose to study medicine in English again. The study revealed that the majority of the participants did not feel that English is a significant barrier in their studies with 62.7% disagreeing with the existence of language barriers. على الرغم من أن اللغة الإنجليزية تعتبر لغة أجنبية، إلا أنها وسيلة التدريس في العديد من كليات الطب في العالم العربي، مما يخلق حواجز لغوية وصعوبات للطلاب. الهدف من هذه الدراسة هو تقييم مخاوف ومواقف الطلاب تجاه اللغة الإنجليزية كلغة تدريس واستكشاف الحواجز وتأثيرها على أدائهم الأكاديمي. كانت هذه دراسة وصفية مقطعية استهدفت الطلاب المسجلين في المرحلة السريرية في كلية الطب بجامعة طرابلس، باستخدام استبيان يُملأ ذاتياً. خلال الفترة من 10 مارس 2024 إلى 24 مارس 2024. أظهر61 طالبًا (36.1%) من طلاب الطب أنهم يشعرون بالراحة مع اللغة الإنجليزية، في مقابل 10 طلاب (5.9%) كانوا غير مرتاحين للغاية. ولم ير معظم المستجيبين أن مشكلة اللغة تجعل الدراسة أصعب وأوصى الأغلبية 102 (60.4%) بإجراء تغييرات لمعالجة القضايا اللغوية في المنهج الدراسي. من بين 66 مشاركًا أجابوا عن هذا القسم، أوصى 33.3% بأن توفر الجامعة دورات لغة إنجليزية مجانية، وذكر 161 طالبًا (95.3%) أنهم سيختارون دراسة الطب باللغة الإنجليزية مرة أخرى. كشفت الدراسة أن غالبية المشاركين لم يشعروا بأن اللغة الإنجليزية تشكل حاجزًا كبيرًا في دراستهم، حيث رفض 62.7% منهم وجود حواجز لغوية